Intervalos de referência para exames laboratoriais de cães da região de Santa Maria, Rio Grande do Sul, Brasil - Bonamigo, Renata (2022)
Reference values for laboratory tests are those considered normal to be expected in healthy animals, and which can be used in the interpretation of laboratory test results. Interpreting laboratory test results using inappropriate reference ranges can result in misinterpretations. Therefore, it is desirable to establish local or specific reference intervals to improve interpretation and assist in clinical decisions. The aim of this study was to determine the reference values for complete blood count and serum biochemical analytes comprising alanine aminotransferase, urea, alkaline phosphatase (ALP), total protein, globulin, albumin and creatinine, for young and adult dogs, as well as for creatinine concentration according to the body size. It was also to compare the analytes studied between young people and adults and between sizes for creatinine concentration. A total of 994 medical records of healthy dogs treated at the University Veterinary Hospital for blood donation or elective surgical procedures were reviewed, corresponding to the years 2015 to 2021, and 250 of these were selected. Data were submitted to statistical analysis, outliers were excluded and reference intervals were calculated with a 90% confidence interval (CI), using the Reference Value Advisor program, which follows the guidelines recommendations of the American Society for Veterinary Clinical Pathology (ASVCP). For comparison of analytes between youth and adults and creatinine concentration between sizes, specific statistical programs were used. A non-statistical comparison was also performed between the results obtained and the RIs proposed in the literature. There was a significant difference (p>0.05) between juveniles and adults for lymphocyte counts and serum ALP activity, which were higher in young dogs; and concentration of globulins, plasma and total serum proteins, higher in adults. The analysis regarding the sizes showed that small dogs have lower concentrations of creatinine (P>0.05) in comparison to medium and large dogs. The upper limit of the reference ranges for eosinophils and ALP were considered of relevance compared to the wide range for the canine species reported in the literature. The findings found can be attributed to greater antigenic and osteoblastic stimulation in young animals, associated with an increase in globulins in adult animals. The creatinine difference can be attributed to lower muscle mass in small dogs. The increase in eosinophil counts was attributed to parasitosis or population characteristics. It is concluded that evaluating specific RIs according to age is necessary due to the higher number of lymphocytes and ALP activity in young dogs and higher concentration of serum proteins, total proteins and globulins in adults. Assessing the creatinine concentration according to the size is important due to the lower concentration of this analyte in small dogs. We concluded the lymphocytes number and ALP activity were higher in young dogs, and the total and globulin proteins serum concentrations were higher in adults; creatinine concentration was lower in small animals. Futhermore, the population studied has its own characteristics not yet represented in other studies, with higher values for eosinophils number and ALP activity in the population of healthy adult and young dogs. Thus, the RIs proposed in this study for the canine species according to age and size, can be used in clinical and surgical routine in the region of Santa Maria - RS, Brazil.